Women's periodicals and print culture in Britain, 1690-1820s : the long eighteenth century - Batchelor, Jennie, 1976-; Powell, Manushag N. (Edinburgh history of women's periodical culture in Britain., 2018)
"This innovative volume presents for the first time collective expertise on women's magazines and periodicals of the long eighteenth century. While this period witnessed the birth of modern periodical culture and its ability to shape aspects of society from the popular to the political, most studies have traditionally obscured the very active role women's voices and women readers played in shaping the periodicals that in turn shaped Britain. The 30 essays here demonstrate the importance of periodicals to women, the importance of women to periodicals, and, crucially, they correct the destructive misconception that the more canonized periodicals and popular magazines were enemy or discontinuous forms. This collection shows how both periodicals and women drove debates on politics, education, theatre, celebrity, social practice, popular reading and everyday life itself. Divided into 6 thematic parts, the book uses innovative methodologies for historical periodical studies, thereby mapping new directions in eighteenth-century and Romantic studies, women's writing as well as media and cultural history."--Back cover